Is the international border effect larger than the domestic border effect? : evidence from U.S. trade - Cletus C. Coughlin; Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2009)
Many studies have found that international borders represent large barriers to trade. But how do international borders compare to domestic border barriers? We investigate international and domestic border barriers in a unified framework. We consider a unique data set of exports from individual U.S. states to foreign countries and combine it with trade flows within and between U.S. states. After controlling for distance and country size, we find that relative to state-to-state trade, crossing an individual U.S. state's domestic border entails a larger trade barrier than crossing the international U.S. border. This finding highlights the concentration of trade flows at the local level and the importance of factors such as informational barriers and transportation costs even for the relatively short distances associated with state-to-state trade.
Keywords: F10; F15; 330; international border effects; intranational home bias; domestic borders; gravity; trade costs; Grenze; Außenwirtschaft; Interregionaler Handel; Transportkosten; Gravitationsmodell; Vergleich; Schätzung; USA